2018
DOI: 10.1111/1462-2920.14372
|View full text |Cite
|
Sign up to set email alerts
|

How Lactobacillus plantarum shapes its transcriptome in response to contrasting habitats

Abstract: Triplets of Lactobacullus plantarum strains were isolated from nine contrasting habitats. Without any passage through other culture media, isolation and cultivation were on model media that strictly reproduced the chemical and physical conditions and stressors of the habitats of origin. Here, we demonstrated how L. plantarum regulates and shapes its transcriptome in response to contrasting habitats. Firstly, multivariate clustering analysis of transcriptional data (RNA-Seq), complemented with metabolomics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Possible mechanisms for microbial bioconversion could be (a) caffeic acid produced by hydroxylation of p-coumaric acid at the meta position similar to Streptomyces caeruleus (Sachan et al, 2006); (b) caffeic acid produced by the o-demethylation of ferulic acid. This pathway was shown in Enterobacter cloacae and Clostridium methoxybenzovorans and in human colonic fermentation of rye bran fortified bread (Micard et al, 2002;Filannino et al, 2014). Filannino et al (2014) had confirmed the ability of some lactic acid bacteria such as Lactobacillus spp.…”
Section: Impact Of Fermentation and In Vitro Digestion On Bioactive Cmentioning
confidence: 61%
See 1 more Smart Citation
“…Possible mechanisms for microbial bioconversion could be (a) caffeic acid produced by hydroxylation of p-coumaric acid at the meta position similar to Streptomyces caeruleus (Sachan et al, 2006); (b) caffeic acid produced by the o-demethylation of ferulic acid. This pathway was shown in Enterobacter cloacae and Clostridium methoxybenzovorans and in human colonic fermentation of rye bran fortified bread (Micard et al, 2002;Filannino et al, 2014). Filannino et al (2014) had confirmed the ability of some lactic acid bacteria such as Lactobacillus spp.…”
Section: Impact Of Fermentation and In Vitro Digestion On Bioactive Cmentioning
confidence: 61%
“…This pathway was shown in Enterobacter cloacae and Clostridium methoxybenzovorans and in human colonic fermentation of rye bran fortified bread (Micard et al, 2002;Filannino et al, 2014). Filannino et al (2014) had confirmed the ability of some lactic acid bacteria such as Lactobacillus spp. to convert protocatechuic acid to catechol; p-coumaric to phloteric acid or p-vinylphenol.…”
Section: Impact Of Fermentation and In Vitro Digestion On Bioactive Cmentioning
confidence: 61%
“…The free phenolics profile was characterized by the products of microbial metabolism of phenolic acids and their derivatives especially in eBSG and fermented BSG. Dihydroferulic, dihydrocaffeic, and phloretic acids are, in fact, the products of ferulic, caffeic, and coumaric acid reduction, respectively (Filannino et al, 2014). Overall, the highest metabolites concentration was found in eBSG fH46.…”
Section: Discussionmentioning
confidence: 93%
“…These bacteria appear to have diversified at the strain level (Siezen et al ., ; Broadbent et al ., ). However, in spite of this diversity, generalist LAB have relatively conserved, core metabolic response pathways (Filannino et al ., ). Under this classification, generalist species include L. plantarum , Lactobacillus casei , Lactobacillus brevis , as well as Lactococcus lactis , L. mesenteroides and W. cibaria (Duar et al ., ) (Fig.…”
Section: Generalist Plant‐associated Labmentioning
confidence: 97%
“…Strains of L. plantarum , L. mesenteroides , L. fermentum , L. brevis and Weissella are able to tolerate high levels of antimicrobial plant phenolic compounds (Filannino et al ., b). Tolerance is likely due to the conversion of these compounds into less toxic metabolites by glycolyl hydrolase, phenolic acid decarboxylase and reductase, and esterase activities (Filannino et al ., ).…”
Section: Characteristics Of Lab Relevant For Colonization Of Plant Sumentioning
confidence: 99%